The effects of the European Single Market on attractiveness to foreign direct investment - Iulia Siedschlag (EconPol Forum, 2023)
The European Single Market has been a major driver of enhanced attractiveness of EU countries to foreign direct investment (FDI). Higher FDI by multinational firms in EU countries has fostered productivity and employment growth and has also generated wider benefits to host economies via knowledge spillovers on the productivity and trade performance of domestic firms. The completion of the Single Market, especially in the areas of services and capital markets, could further increase trade and investment in EU countries. Removing regulatory barriers at both the EU and member states levels in the areas of services could strengthen the integration of business services in key manufacturing sectors and could result in a more efficient integration of firms in European and global value chains. An integrated Single Market for capital would improve financing and investment opportunities for European firms
Keywords: 330